Application of multiplex SNaPshot assay in measurement of PLAC4 RNA‐SNP allelic ratio for noninvasive prenatal detection of trisomy 21. (20th December 2013) - Yang, Lan; Sun, Haiyan; Chen, Daozhen; Lu, Mudan; Wang, Junfeng; Xu, Fei; Hu, Lingqing; Xiao, Jianpin
ABSTRACT Objective For the samples in which the fetus was heterozygous for the placenta‐specific 4 (PLAC4) single‐nucleotide polymorphism (SNP), our research is to develop a rapid, accurate, and cost‐effective assay for the noninvasive prenatal detection of fetal trisomy 21 (T21). Method Maternal plasma samples were prepared from 60 euploid pregnancies (range: 15–23 weeks) to 17 T21 pregnancies (range: 19–26 weeks). With the application of the SNaPshot assay in measuring the PLAC4 RNA‐SNP allelic ratio, we can achieve noninvasive prenatal detection of T21. Also we detected the genotypes of SNP located in gene PLAC4 in samples collected in Southeast China of 216 volunteers. Results Of all 77 singleton pregnancies, 21 gravidas were found heterozygous for the PLAC4 SNP. Among them, four pregnancies with a T21 fetus and 17 pregnancies with a euploid fetus were detected. The SNPs with higher heterozygosity rates on gene PLAC4 were Rs8130833 and Rs4818219, which were estimated to be 0.278 and 0.343, respectively. Conclusion For samples with heterozygous SNPs, the PLAC4 RNA‐SNP allelic ratio approach can be used for noninvasive prenatal detection of T21 by the multiplex SNaPshot assay. The two SNPs with higher frequency of heterozygosity on gene PLAC4 were Rs8130833 and Rs4818219 in population of Southeast China. © 2013 John Wiley & Sons, Ltd.